Immune Cell-Type Specific Ablation of Adapter Protein ADAP Differentially Modulates EAE - Rudolph, Jochen; Meinke, Clara; Voss, Martin; Guttek, Karina; Kliche, Stefanie; Reinhold, Dirk; Schraven, Burkhart; Reinhold, Annegret (Frontiers in Immunology, 2019)
The cytosolic adhesion and degranulation-promoting adapter protein ADAP is expressed in various hematopoietic cells including T cells, NK cells, myeloid cells, and platelets but absent in mature B cells. The role of ADAP in T cell activation, proliferation and integrin activation is well accepted. We previously demonstrated that conventional ADAP knockout mice show a significantly attenuated course of experimental autoimmune encephalomyelitis (EAE). To dissect the impact of different ADAP expressing cell populations on the reduced EAE severity, here, we generated lineage-specific conditional knockout mice. ADAP was deleted in T cells, myeloid cells, NK cells and platelets, respectively. Specific loss of ADAP was confirmed on the protein level. Detailed immunophenotyping was performed to assess the consequence of deletion of ADAP with regard to the maturation and distribution of immune cells in primary and secondary lymphoid organs. The analysis showed equivalent results as for conventional ADAP knockout mice: impaired thymocyte development in ADAPfl/fl Lck-Cre mice, normal NK cell and myeloid cell distribution in ADAPfl/fl NKp46-Cre mice and ADAPfl/fl LysM-Cre mice, respectively as well as thrombocytopenia in ADAPfl/fl PF4-Cre mice. Active EAE was induced in these animals by immunization with the myelin oligodendrocyte glycoprotein35-55 peptide. The clinical course of EAE was significantly milder in mice with loss of ADAP in T cells, myeloid cells and NK cells compared to ADAP-sufficient control littermates. Surprisingly, specific deletion of ADAP in platelets resulted in a more exacerbated disease. These data show that T cell-independent as well as T cell-dependent mechanisms are responsible for the complex phenotype observed in conventional ADAP knockout mice.